Pelaksanaan Ekstrakurikuler Bernyanyi Di SMP Negeri 3 Lubuk Sikaping - Sherina Avelya Wedyan; Harisnal Hadi (Institut Nalanda, 2023)
This study aims to determine students' interest in extracurricular singing at SMP Negeri 3 Lubuk Sikaping and what factors influence students' interest in participating in extracurricular singing activities at SMP Negeri 3 Lubuk Sikaping. The research method applied in this study is a descriptive approach in the form of qualitative research. The tools used in this study are the researchers themselves who are actively involved in making direct observations in the field as the main method for collecting data. The data used consists of primary and secondary data, which are collected through observation, interviews, literature studies, and document collection. The data analysis process involves the stage of clarification and conclusion of data. Research findings show that the implementation of extracurricular singing at SMP Negeri 3 Lubuk Sikaping which is carried out for the readiness of singing lompa such as FLS2N and other singing competitions has been successfully carried out well, but there are several obstacles in its implementation not in accordance with the activity program so that extracurricular implementation is still less effective. In terms of the approach applied, the teacher has chosen a method that matches the content of the material. However, because cultural arts teachers are teachers who are not competent in the field of music. So that during extracurricular singing implementation, teachers are less able to know singing techniques. Students who follow become less serious when extracurricular activities take place. Therefore, the achievement of the success rate in the implementation of extracurricular singing activities at SMP Negeri 3 Lubuk Sikaping has not been achieved.